Impact of forest fragmentation on river water quality: an example from a typical subtropical hilly basin - Biao Li; Xiaolei Huang; Qiang Zhong; Xiuxiu Wu (PeerJ)
Background Forest fragmentation, driven by natural and human activities, is increasing. However, the impact of forest fragmentation on river water quality remains ambiguous. Methods In this study, water quality data were collected from 15 monitoring sites in the upper Ganjiang River basin in winter and summer, and the forest landscape fragmentation metrics in the sub-basin was calculated to assess its seasonal impact on river water quality. Results The results indicated that water quality in the area is generally satisfactory, with total nitrogen (TN) as the main pollutant. Redundancy analysis (RDA) showed that the explanation rate of the six forest landscape fragmentation metrics to the water quality change in summer was 41.21%, and in winter, their explanation rate of water quality change increased by 14.26%. Among them, the effective mesh size (MESH) was negatively correlated with most river water quality indicators, with a contribution rate of 20.9%. While the interspersion and juxtaposition index (IJI) was positively correlated with most water quality indicators in winter, with a contribution rate of 44.9%. It is worth noting that the thresholds for IJI and MESH of forest were the same in winter and summer, 28.1% and 7.89e+0.5ha, respectively, when the probability of an abrupt change in TN concentration reached 100%. This is implied that when the adjacency of forest patches is less than 28.1% and the connectivity of forest patches is more than 7.89e+0.5ha, it may contribute to the reduction of TN concentration in rivers. These findings provide valuable insights into how varying degrees of forest fragmentation can lead to deterioration in river water quality, and allow for further planning of forest structure based on forest fragmentation thresholds to improve regional water quality.